2008
DOI: 10.1177/1350507608096037
|View full text |Cite
|
Sign up to set email alerts
|

Absorptive Capacity: A Process Perspective

Abstract: Absorptive capacity is regarded as an important factor in both corporate innovation and general competitive advantage. The concept was initially developed largely from reviews of the literature and has subsequently been extended by empirical studies, although some people suggest that progress since 1990 has been disappointing. This article argues that this limited development results from the dominance of quantitative studies which have failed to develop insights into the processes of absorptive capacity, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
221
0
16

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 169 publications
(248 citation statements)
references
References 30 publications
11
221
0
16
Order By: Relevance
“…Figure 2 shows our revised model of green ACAP when considered from a standards implementation perspective. The three antecedents identified by Gluch et al (2009) directly affect the knowledge acquisition phase; it is widely accepted in the literature that this precedes the assimilation phase (Easterby-Smith et al, 2008;Gluch et al, 2009;Zahra and George, 2002). Assimilation of knowledge is typically actioned through training programmes, which open up learning opportunities and hence can influence employee values and beliefs (Linnenluecke and Griffiths, 2010) as well as the organisation's ACAP (Gann, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Figure 2 shows our revised model of green ACAP when considered from a standards implementation perspective. The three antecedents identified by Gluch et al (2009) directly affect the knowledge acquisition phase; it is widely accepted in the literature that this precedes the assimilation phase (Easterby-Smith et al, 2008;Gluch et al, 2009;Zahra and George, 2002). Assimilation of knowledge is typically actioned through training programmes, which open up learning opportunities and hence can influence employee values and beliefs (Linnenluecke and Griffiths, 2010) as well as the organisation's ACAP (Gann, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…ACAP as a dynamic capability means that it can be attributed to a collective such as the firm or to individual employees or innovation managers. Individual absorptive capacity, at the level of tourism change agents, draws attention to the ability to appreciate and acquire knowledge from the external environment; however, it also focuses on the ability to engage in the internal processes of learning (Easterby-Smith et al, 2008).…”
Section: Absorptive Capabilitymentioning
confidence: 99%
“…The concept of ´absorptive capability´ (ACAP) assumes that firms have varying capabilities in terms of knowledge absorption and the application of knowledge in innovation processes (Easterby-Smith, Graça Antonacopoulou, & Ferdinand 2008). Zahra and George (2002) suggested that ACAP encompasses both the acquisition and assimilation (the potential ACAP) and the transformation and realization (the realized ACAP) of knowledge.…”
Section: Introductionmentioning
confidence: 99%
“…In modelling ACAP using a process view (similar to that of Easterby-Smith et al, 2008), four dimensions have been identified -as shown in Zahra and George's (2002) model (Figure 1). Also shown are activation triggers (that is, external -the change in the construction market's requirements; and internal -the organization forming a partnership to address the challenge at all levels), socialization mechanisms to incorporate and use new knowledge, gatekeepers who hold key roles in knowledge filtering and transfer, and boundary spanners who transcend organizational silos and help spread knowledge to all areas and levels of the organization.…”
Section: Developing An Absorptive Capacity Perspective and Research Qmentioning
confidence: 99%
“…However, Jones (2006), along with Zahra and George (2002), states that the study of ACAP in organizations is limited by a lack of definition at an operational level within these organizations. Easterby-Smith et al (2008) conclude that there is a need for further studies in different types of organizations to develop further understanding of the construct and adopt a process approach to ACAP. Hence, the main aim of this paper is to explore how dynamic capability using an absorptive capacity framework in response to these challenges has been developed within a construction-based SME (which specializes in public contracts).…”
mentioning
confidence: 99%